The Growing Cybersecurity Crisis in Healthcare: A Call to Action (American Journal of Innovation in Science and Engineering, 2024)
Electronic healthcare technology is pervasive throughout the globe, and it affords vast opportunities to enhance clinical outcomes, as well as for the transformation of models of care. Concerns are, however, growing, related to healthcare data and device security. Increased connectivity to legacy computer networks brought cybersecurity vulnerabilities for medical devices. Healthcare represents an attractive target for cybercrime because healthcare data is precious. This sector in present times is full of unique cybersecurity challenges, especially for susceptible kinds of patient information at stake. Second, many legacy systems will be prevalent—not adding more to that—with the changing face of cyber threats. Cybersecurity breaches have comprised stealing health information and focused ransomware attacks on hospitals; this could mean as vivid an attack as on implanted medical devices. This only points to the fact that ransomware attacks and other kinds of cyber-attacks against hospitals and other medical facilities are gaining ground; there is every reason to get alarmed and put in place stricter cybersecurity measures. An excellent healthcare cybersecurity strategy, therefore, has to consider access control, intrusion detection systems, encryption techniques, and periodic security testing. Data breaches and cyber-attacks are forcing any healthcare provider to invest in new state-of-the-art technologies related to keeping pace with trends regarding cybersecurity. The dangers that can be caused by cyber-attack include a considerable diminution in patient trust, potential health system collapse, human life threats, etc. On the whole, cybersecurity is strenuously linked with the question of patient safety.